A Skyrme Model with Novel Chiral Symmetry Breaking - Sutcliffe, Paul (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
An extension of the Skyrme model is presented in which derivative terms are added that break chiral symmetry to isospin symmetry. The theory contains just one new parameter, and it reduces to the standard Skyrme model when this symmetry-breaking parameter vanishes. The same Faddeev-Bogomolny energy bound applies for all parameter values, but the parameter can be tuned so that the energy of the single Skyrmion is much closer to the bound than in the standard Skyrme model. Applying the rational map approximation to multi-Skyrmions suggests that, for a suitable value of the symmetry-breaking parameter, binding energies in this theory may be significantly more realistic than in the standard Skyrme model.